2015
DOI: 10.1111/iju.12859
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal versus ventral onlay buccal mucosal graft urethroplasty for long‐segment bulbar urethral stricture: A prospective randomized study

Abstract: Objectives: To compare safety and efficacy of ventral versus dorsal onlay buccal mucosal graft urethroplasty in patients with long-segment incomplete bulbar urethral stricture.Methods: This was a single center, prospective, randomized trial. Patients with longsegment (>2 cm) incomplete bulbar urethral stricture and meeting eligibility criteria were enrolled in the study. They were randomized into two study groups: group A undergoing dorsal onlay buccal mucosal graft urethroplasty and group B undergoing ventral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Ventral and dorsal onlay urethroplasties are the most popular types of substitution urethroplasty, and the different graft positions (ventral or dorsal) have shown no difference in success rate in bulbar urethroplasty. 43,44 When a bulbar urethral stricture has an obliterative or nearly obliterative segment, neither EPA nor an onlay procedure is possible, because such a stricture contains a significant amount of spongiofibrosis that would potentially risk the success of the graft or flap, and because the length of excised urethra would result in too much tension on anastomosis. One solution for this kind of stricture is a combination of EPA and primary anastomosis and onlay augmentation, a combination called an augmented anastomotic urethroplasty.…”
Section: Bulbar Urethral Stricturementioning
confidence: 99%
“…Ventral and dorsal onlay urethroplasties are the most popular types of substitution urethroplasty, and the different graft positions (ventral or dorsal) have shown no difference in success rate in bulbar urethroplasty. 43,44 When a bulbar urethral stricture has an obliterative or nearly obliterative segment, neither EPA nor an onlay procedure is possible, because such a stricture contains a significant amount of spongiofibrosis that would potentially risk the success of the graft or flap, and because the length of excised urethra would result in too much tension on anastomosis. One solution for this kind of stricture is a combination of EPA and primary anastomosis and onlay augmentation, a combination called an augmented anastomotic urethroplasty.…”
Section: Bulbar Urethral Stricturementioning
confidence: 99%
“…Vasudeva et al [12] 92.5% (n=40) ------90% (n=40) ly rather than dorsally and even dorso-laterally. This was especially true when the stricture was localized more proximally in bulbar urethra and the spatulation displaced the anastomotic site more proximally.…”
Section: Discussionmentioning
confidence: 90%
“…On review of literature it was found that both dorsal and ventral BMG augmentation urethroplasties were associated with similar outcomes (Table 2). [9][10][11][12] Proponents of dorsal placement of graft argue that there is decreased chance of diverticula formation and better chance of neovascularisation with the graft lying on cavernosal bodies which would not be seen if the graft is placed ventrally. The proponents of ventral placement in bulbar urethra argue that it offers better access to proximal site of stricture, less mobilization of urethra preserving its vascularity in addition to the fact that the bulbocavernous muscle prevents diverticula formation.…”
Section: Discussionmentioning
confidence: 99%
“…Most urologists believe the concept of ‘reconstructive ladder', the basic tenet of which entails resorting to the minimally invasive surgeries namely Balloon dilation or VIU and resorting to a formal urethroplasty as the last resort [6]. The variants of the latter could include an end-to-end or substitution/augmentation urethroplasty, depending on the length and site of stricture [7]. The need for general anesthesia, prolonged surgery and hospital stay, longer catheterization, necessary surgical expertise and patient selection are pitfalls of the procedure.…”
Section: Discussionmentioning
confidence: 99%